2013
DOI: 10.3892/mmr.2013.1385
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism through which octreotide inhibits hepatic stellate cell activity

Abstract: Hepatic stellate cells (HSCs) are important in the development of liver fibrosis and in the pathogenesis of portal hypertension. Octreotide, an analogue of somatostatin, has been demonstrated to effectively treat fibrosis and portal hypertension; however, its relative mechanism in HSCs remains unknown. LX‑2, the immortalized HSC line, was used to study the mechanism whereby octreotide functions at different concentrations. Real‑time polymerase chain reaction (PCR) and western blot analysis were used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…Again, this effect could be mediated in a paracrine fashion, since fibroblasts express both cortistatin and its receptors (this study, Borie et al, 2008;Egger et al, 2014;Tug et al, 2013), and here we observed that exogenously added cortistatin inhibited directly the expression of several mediators and markers of fibrosis by TGFβ1-activated fibroblasts. In agreement, various studies reported the effect of cortistatin in MAPKs and Akt in other cell types (Duran-Prado et al, 2013;Morell et al, 2014), and other sstr-agonists regulate the activation of fibroblasts (Borie et al, 2008;Wang et al, 2013). Moreover, by using specific antagonists, we provide the evidence that sstr and GHSR play major roles in the anti-fibrotic effects of cortistatin in the lung.…”
Section: Discussionsupporting
confidence: 89%
“…Again, this effect could be mediated in a paracrine fashion, since fibroblasts express both cortistatin and its receptors (this study, Borie et al, 2008;Egger et al, 2014;Tug et al, 2013), and here we observed that exogenously added cortistatin inhibited directly the expression of several mediators and markers of fibrosis by TGFβ1-activated fibroblasts. In agreement, various studies reported the effect of cortistatin in MAPKs and Akt in other cell types (Duran-Prado et al, 2013;Morell et al, 2014), and other sstr-agonists regulate the activation of fibroblasts (Borie et al, 2008;Wang et al, 2013). Moreover, by using specific antagonists, we provide the evidence that sstr and GHSR play major roles in the anti-fibrotic effects of cortistatin in the lung.…”
Section: Discussionsupporting
confidence: 89%
“…Somatostatin and its analogues are known to curb HSC activation [15] and have been seen to attenuate liver fibrosis/fibrogenesis in other forms of liver injury [42][43][44]. Reynaert and colleagues demonstrated that somatostatin administration reduced both gene and protein expression of α-SMA and collagens I and III by HSCs in vitro [45].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that over deposition of ECM can impair the liver function and collagen is the main component of ECM produced by activited HSCs [ 20 ]. In activated HSCs, down-regulation of SP1 is able to inhibit the proliferation and the expression of TGF-β, α-SMA and Smad4 [ 21 ]. In human hypertrophic scar fibroblasts, SP1 Decoy ODN can significantly reduce the secretion of collagen [ 22 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%